2003
DOI: 10.1016/s0735-1097(03)00426-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of atrial pacing therapies on atrial tachyarrhythmia burden and frequency

Abstract: This DDDRP pacemaker is safe, has accurate AT/AF detection, and provides ATP with 54% efficacy as defined by the device. The atrial prevention and termination therapies combined did not reduce AT/AF burden or frequency in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(22 citation statements)
references
References 9 publications
2
18
0
1
Order By: Relevance
“…4,6,3032 Two recent trials, such as the ASSERT and the SAFE studies, did not find a substantial benefit of continuous atrial overdrive pacing in preventing AF occurrence. 4,30 However, it is important to note that both these studies tested only one prevention algorithm, while MINERVA trial tested three preventive algorithms together with aATP and MVP.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,3032 Two recent trials, such as the ASSERT and the SAFE studies, did not find a substantial benefit of continuous atrial overdrive pacing in preventing AF occurrence. 4,30 However, it is important to note that both these studies tested only one prevention algorithm, while MINERVA trial tested three preventive algorithms together with aATP and MVP.…”
Section: Discussionmentioning
confidence: 99%
“…The ATTEST trial evaluated three different algorithms for AF prevention (Atrial Preference Pacing, Atrial Rate Stabilization and Post Mode Switching Overdrive), and showed no difference in total number of AF episodes or median AF burden between patients with either the algorithms switched "on" or "off" [39]. The PIPAF trial had similar results, showing no difference in number of AF paroxysms per week in a crossover population during a 3 months follow up [40].…”
Section: Trigger Suppression Algorithmsmentioning
confidence: 99%
“…Efficacy of atrial ATP is low, mainly because of the aforementioned mechanisms, and it varies from 30 to 54% [39]. However, several variables must be taken into account.…”
Section: Atrial Pacing For Af Terminationmentioning
confidence: 99%
“…Paroxysmale Vorhoftachyarrhythmien stellen nach negativen Studienergebnissen [16,17,18,19,20,21] keine primäre Schrittmacherindikation dar. Die deutschen Leitlinien legen deshalb nur fest, unter welchen Bedingungen präventive Stimulation jenseits klassischer Indikationen eingesetzt werden darf (IIa-C, IIb-C); (.…”
Section: Vorhofflimmernunclassified